Apoptotic signaling in mouse odontogenesis - Matalova, Eva; Svandova, Eva; Tucker, Abigail S (Omics, 2012)
Apoptosis is an important morphogenetic event in embryogenesis as well as during postnatal life. In the last 2 decades, apoptosis in tooth development (odontogenesis) has been investigated with gradually increasing focus on the mechanisms and signaling pathways involved. The molecular machinery responsible for apoptosis exhibits a high degree of conservation but also organ and tissue specific patterns. This review aims to discuss recent knowledge about apoptotic signaling networks during odontogenesis, concentrating on the mouse, which is often used as a model organism for human dentistry. Apoptosis accompanies the entire development of the tooth and corresponding remodeling of the surrounding bony tissue. It is most evident in its role in the elimination of signaling centers within developing teeth, removal of vestigal tooth germs, and in odontoblast and ameloblast organization during tooth mineralization. Dental apoptosis is caspase dependent and proceeds via mitochondrial mediated cell death with possible amplification by Fas-FasL signaling modulated by Bcl-2 family members.
Keywords: Animals; lidé; Apoptosis; Signal Transduction; zubní zárodek; Tooth Germ; signální transdukce; Odontogenesis; Mice; kaspasy; Humans; odontogeneze; Caspases; apoptóza; myši; zvířata